Medium term effects of including manual therapy in a pulmonary rehabilitation program for chronic obstructive pulmonary disease (COPD): a randomized controlled pilot trial. (14th March 2016) - Engel, Roger Mark; Gonski, Peter; Beath, Ken; Vemulpad, Subramanyam
Abstract : Study design: Randomized clinical trial. Objective: To investigate the effect of including manual therapy (MT) in a pulmonary rehabilitation program for patients with chronic obstructive pulmonary disease (COPD). Background: The primary source of exercise limitation in people with COPD is dyspnea. The dyspnea is partly caused by changes in chest wall mechanics, with an increase in chest wall rigidity (CWR) contributing to a decrease in lung function. As MT is known to increase joint mobility, administering MT to people with COPD carries with it the potential to influence CWR and lung function. Methods: Thirty-three participants with COPD, aged between 55 and 70 years (mean = 65·5±4 years), were randomly assigned to three groups: pulmonary rehabilitation (PR) only, soft tissue therapy (ST) and PR, and ST, spinal manipulative therapy (SM), and PR. Outcome measures including forced expiratory volume in the 1st second (FEV1 ), forced vital capacity (FVC), 6-minute walking test (6MWT), St. George's respiratory questionnaire (SGRQ), and the hospital anxiety and depression (HAD) scale were recorded at 0, 8, 16, and 24 weeks. Results: There was a significant difference in FVC between the three groups at 24 weeks ( P  = 0·04). For the ST+SM+PR group versus PR only the increase was 0·40 l (CI: 0·02, 0·79; P  = 0·03). No major or moderate adverse events (AE) were reported following the administration of 131 ST and 272 SM interventions. Discussion: The increase in FVC is a unique finding. Although the underlying mechanisms responsible for this outcome are not yet understood, the most likely explanation is the synergistic effect resulting from the combination of interventions. These results support the call for a larger clinical trial in the use of MT for COPD.